Ventriculo-Arterial Coupling Is Associated With Oxygen Consumption and Tissue Perfusion in Acute Circulatory Failure - Andrei, Stefan; Nguyen, Maxime; Longrois, Dan; Popescu, Bogdan A.; Bouhemad, Belaid; Guinot, Pierre-Grégoire (Frontiers in Cardiovascular Medicine, 2022)
Introduction The determination of ventriculo-arterial coupling is gaining an increasing role in cardiovascular and sport medicine. However, its relevance in critically ill patients is still under investigation. In this study we measured the association between ventriculo-arterial coupling and oxygen consumption (VO2) response after hemodynamic interventions in cardiac surgery patients with acute circulatory instability. Material and Methods Sixty-one cardio-thoracic ICU patients (67 ± 12 years, 80% men) who received hemodynamic therapeutic interventions (fluid challenge or norepinephrine infusion) were included. Arterial pressure, cardiac output, heart rate, arterial (EA), and ventricular elastances (EV), total indexed peripheral resistances were assessed before and after hemodynamic interventions. VO2 responsiveness was defined as VO2 increase > 15% following the hemodynamic intervention. Ventriculo-arterial coupling was assessed measuring the EA/EV ratio by echocardiography. The left ventricle stroke work to pressure volume area ratio (SW/PVA) was also calculated. Results In the overall cohort, 24 patients (39%) were VO2 responders, and 48 patients had high ventriculo-arterial (EA/EV) coupling ratio with a median value of 1.9 (1.6-2.4). Most of those patients were classified as VO2 responders (28 of 31 patients, p=0.031). Changes in VO2 were correlated with those of indexed total peripheral resistances, EA, EA/EV and cardiac output. EA/EV ratio predicted VO2 increase with an AUC of 0.76 [95 % CI: 0.62-0.87]; p=0.001. In principal component analyses, EA/EV and SW/PVA ratios were independently associated (p<0.05) with VO2 response following interventions. Conclusions VO2 responders were characterized by baseline high ventriculo-arterial coupling ratio due to high EA and low EV. Baseline EA/EV and SW/PVA ratios were associated with VO2 changes independently of the hemodynamic intervention used. These results underline the pathophysiological significance of measuring ventriculo-arterial coupling in patients with hemodynamic instability, as a potential therapeutic target.